Interação da espécie de madeira e do tipo de adesivo na qualidade da madeira laminada colada - Oliveira, Stefânia Lima (2016)
The glued laminated timber is considered as a good material for structural use. This technique is based on the rational use of low and medium density wood, with using of smaller parts. In addition to the appropriate adhesive selection, the knowledge of the physical, mechanical, chemical and anatomical of wood allows better use of this as a structural material. Thus, the objective in this study was to evaluate the use of new wood species for glued laminated timber production and interaction wood/adhesive. Four wood species were used: Cedrelinga catenaeformis (Cedrão), Eucalyptus grandis (Eucalipto), Castilla ulei Warb. (Caucho) and Acrocarpus fraxinifolius (Cedro Indiano); and two adhesive types: resorcinol and polyurethane on castor oil base. These woods were prepared and classified using the non-destructive method and passed for physical, mechanical, chemical and anatomical characterization. Subsequently the classification was made glued laminated timber using polyurethane adhesive on castor oil base and resorcinol, the weight 350 g/m², pressing pressure of 1 MPa and 24h pressing time. Tests physical and mechanical, as well as delamination and non-destructive assay were carried out. There was a significant interaction between the adhesive and the wood type when measured the properties compression and elasticity and rupture modulus to static bending the beams. In both properties, Eucalipto wood obtained the best results, followed by the Cedro Indiano wood, which presented the best glue. The dhesive type affects only the post-boil shear property of beams, the resorcinol adhesive was the most resistant. Overall, the resorcinol and polyurethane adhesives on castor oil base can be used for beams production of glued laminated timber with Eucalipto, Cedro Indiano, Caucho and Cedrão woods. As in some cases necessary process adjustments.